2005
DOI: 10.1007/s11892-005-0039-7
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life among adults with diabetes

Abstract: Diabetes has significant effects on quality of life; however, the interrelationships are complex among the physiologic and psychosocial effects of diabetes, the effects of treatment regimens, and the social and cultural contexts in which we live. These important relationships and effects are being defined, but much additional work is needed to reliably and accurately measure health-related quality of life among subpopulations, and to measure and optimize the effects of increasingly complex and intensive treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
27
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 60 publications
4
27
0
1
Order By: Relevance
“…In our study, glycemic control was not associated with HRQoL while patients with complications showed lower QoL scores than patients without complications, though this difference was not statistically significant. Additionally, men with T2DM reported higher scores in present QoL than women, a finding consistent with other studies in similar populations (9,12,(26)(27)(28)(29). Several studies showed that the most negatively impacted domains were those related to food, namely, 'freedom to eat', 'enjoyment of food' and 'freedom to drink'.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, glycemic control was not associated with HRQoL while patients with complications showed lower QoL scores than patients without complications, though this difference was not statistically significant. Additionally, men with T2DM reported higher scores in present QoL than women, a finding consistent with other studies in similar populations (9,12,(26)(27)(28)(29). Several studies showed that the most negatively impacted domains were those related to food, namely, 'freedom to eat', 'enjoyment of food' and 'freedom to drink'.…”
Section: Discussionsupporting
confidence: 89%
“…Sundaram et al (33) also reported that older age (60 years of age) was independently associated with higher ADDQoL scores in a multivariate analysis. Differences between genders were also seen in domains such as sex life, friendship and social life and enjoyment of food, which is consistent with findings in other studies (9,26). Our main limitation is that the study sample was drawn from specialized diabetes clinics rather than randomly selected centers, affecting the generalizability of our findings.…”
Section: Discussionsupporting
confidence: 87%
“…4,5 Patients diagnosed with CVD generally report worse health-related QoL than patients with type 2 diabetes only, 6 and an incremental effect has been suggested in patients with both diseases. 7,8 The prognostic value of health-related QoL has been established in patients with chronic illnesses such as heart failure 9,10 and kidney disease.…”
Section: Introductionmentioning
confidence: 99%
“…1,7 Despite the burden of morbidity that diabetes exerts on individuals and health systems and the availability of interventions to combat this burden, there have been no systematic reviews specifically examining the effect of diverse interventions on HRQL among persons with diabetes. Previously published reviews were either narrative reviews 9,10 or else only focused on how diabetes affected HRQL. 9,11 Thus, the objective of this systematic review is to assess the effect of various interventions on HRQL, as measured by the Short Form (SF)-36 questionnaire, in adults with diabetes.…”
mentioning
confidence: 99%